Building a Sustainable Global Surgical Program in an Academic Department of Surgery - Linda P. Zhang; Daniel Silverberg; Celia M. Divino; Michael Marin (Ubiquity Press, 2016)
Background Global surgery and volunteerism in surgery has gained significant interest in recent years for general surgery residents across the country. However, there are few well-established long-term surgical programs affiliated with academic institutions. The present report discusses the implementation process and challenges facing an academic institution in building a long-term sustainable global surgery program. Methods As one of the pioneer programs in global surgery for residents, the Icahn School of Medicine at Mount Sinai global surgery rotation has been successfully running for the last 10 years in a small public hospital in the Dominican Republic. The present report details many key components of implementing a sustainable global surgery program and the evolution of this program over time. Findings Since 2005, 80 general surgery residents have rotated through Juan Pablo Pina Hospital in the Dominican Republic. They have performed a total of 1239 major operations and 740 minor operations. They have also participated in 328 emergency cases. More importantly, this rotation helped shape residents' sense of social responsibility and ownership in their surgical training. Residents have also contributed to the training of local residents in laparoscopic skills and through cultural exchange. Conclusions As interest in global surgery grows among general surgery residents, it is essential that supporting academic institutions create sustainable and capacity-building rotations for their residents. These programs must address many of the barriers that can hinder maintenance of a sustainable global surgery experience for residents. After 10 years of sending our residents to the Dominican Republic, we have found that it is possible and valuable to incorporate a formal global surgery rotation into a general surgery residency.